Impacts of an early childhood obesity prevention program in Mexico. Issue 4 (10th June 2022) - Flores-Peña, Y; He, M; Sosa, E T; Avila-Alpirez, H; Trejo-Ortiz, P M; Gutiérrez-Sánchez, G
Abstract: The Healthy Change Program aimed to improve the accuracy of maternal perceptions of children's weight (MPCW), maternal feeding style (MFS) and feeding practices. Using a randomized control trial design, the intervention group received 4-weekly group sessions focusing on MPCW, MFS and healthy behaviors. The control group received the same dose of attention-control sessions on food hygiene. Data were collected at the baseline and at the end of the program via self-administered questionnaires and anthropometric measurements. Participants included 294 mother–child dyads with 149 in the intervention group and 145 in the control group. The accuracy of MPCW significantly increased at the study end point in the intervention group (57.0–67.1%, P  < 0.05) but not in the control group (67.6–69.7%, P  > 0.05), with no between-group difference in pre- and post-change ( P  > 0.05). At the study end point, more mothers of overweight and obese children in the intervention group had accurate MPCW than their control counterparts (31.4% versus 11.1%, P  < 0.01). The intervention group had a shift toward an authoritative style at the study end point (17.4% versus 26.2%, P  < 0.001) and favorable changes in feeding practices. The Healthy Change Program contributed to improving the accuracy of MPCW and shifts toward favorable MFS and feeding practices.